Doctrinal Reflection avd Administrative Case Law: What Interaction? (Global Journal of Human-Social Science, 2023)
The doctrinal work constitutes a means of structuring and orienting the jurisdictional process by means of several approaches aiming in particular to examine the source and the basis of a decision of the administrative judge, to establish a definition, to identify an interpretation of the case law, to plead for more protection of the citizens rights or to demonstrate their enthusiasm for case law. The ideal corpus guides, frames and structures the judicial work of administrative courts and court officers and also constitutes a permanent source of information allowing the judge to know how his case law is perceived, understood, felt, approved or criticized. But the doctrine also has, precisely through its critical role, a function of innovation and incitement to change.
Keywords: doctrine - contentious discussion – role - juge- jurisprudence